PERENCANAAN LANSKAP WISATA DI KAWASAN PANORAMA SILEME-LEME, KECAMATAN POLLUNG, HUMBANG HASUNDUTAN - Purba, Ricky Wahyu; Rahmadhani Fitri; Fariz Harindra Syam (PT. Arsil Reka Engineering, 2024)
Panorama Sileme-Leme is a tourist destination in Humbang Hasundutan Regency, precisely in Huta Sileme-Leme, Parsingguran 2 Village, Pollung District which is at an altitude of approximately 1,600 meters above sea level. The beautiful natural panorama with the background ofLake Toba and surrounded by gardens, is very feasible to be used as a place of recreation. However, supporting facilities in this area are not yet adequate to support various recreational activities that have the potential to be carried out in the area. Therefore, it is necessary to do landscapeplanning and provide tourist facilities so that it attracts more tourists to visit. The initial idea of this concept is to plan the Sileme-leme panorama area as an attractive tourist destination and equipped with various supporting facilities for tourist activities. However, because it is located in a hilly area prone to landslides, the concept of pine forest tourism is applied, which in addition to aesthetics and visitor comfort, the main function is to minimize landslides because pine trees are known as good soil retaining vegetation. In addition, the pine forest tourism landscape can also have interesting spots such as tall shady pine trees, restaurants or cafes with pine forest views, and also play areas for children. This helps to enhance visitors' tourism experience and makes them feel close to nature and the beauty of the pine forest. The planningof Sileme-leme Panorama Area uses the concept of a semi pine forest which is added with various tourist facilities. The application of this concept has been considered through various analyses conducted previously. With the application of the semi pine forest concept, it is expected that the natural potential will not change much, and the preservation of nature in this area will be maintained. The existence of this planning isexpected Sileme-leme Panorama to be a tourist attraction that is more developed and more attractive to tourists to visit. In addition, this planning is expected to improve the economy of the local community.